Ethical Governance in Urban Environmental Management: A Nigerian Perspective - Saheed Olaniran; Muslih Faozanudin; Denok Kurniasih (Penerbit Jurnal Indonesia, 2025)
This study examines the critical role of ethical governance in addressing Nigeria's urban environmental challenges exacerbated by rapid urbanization, environmental degradation, and socio-economic disparities. Drawing insights from interviews with relevant stakeholders and case studies from Lagos State, Ibadan, and Niger Delta, the study emphasizes the importance of transparency, accountability, and inclusivity. Through comparative analysis with other nations facing similar challenges and an evaluation of existing environmental laws, the study highlights practical solutions such as green infrastructure integration, technology adoption, and enhanced public participation. The report makes specific recommendations for promoting sustainable, equitable urban development, emphasizing ethical leadership as a foundation for transformative change.